The Influence of Digital Marketing and Attractiveness on Destination Image and Its Impact on Tourist Visiting Decisions to Cirendeu Village - Febri Tri Intan Azhana (Universitas KH. Abdul Chalim Mojokerto, 2025)
The tourism industry has experienced rapid development, especially in this digital era. Digital marketing has become a major force in promoting tourist destinations, and the image of the destination is a key factor in attracting tourists. The natural and cultural attractiveness of a place also plays an important role in shaping the image of the destination. This is becoming increasingly important considering the intense competition between destinations and the potential for economic growth that can be generated by the tourism industry. With a better understanding of the role of digital marketing and attractiveness in influencing a destination's image, tourism destinations can improve their competitiveness and create a positive experience for tourists. This study aims to investigate and analyze the influence of digital marketing and attractiveness on the image of tourism destinations, as well as how it impacts tourists' visiting decisions. The research method used is a quantitative approach. The population in this study is visitors; the sample in this study is obtained by purposive sampling so that the number of samples becomes valid. Data analysis used a structural Equation Model (SEM) approach assisted by smart PLS applications. The results of this study will provide valuable insights for the tourism industry in understanding how digital marketing and destination attractiveness can influence traveller decisions, as well as how to improve a destination's image to attract more tourist visits.